STUDY OF THE DAMAGE DEGREE OF DENT PIPE BASED ON OYANE DUCTILE FRACTURE CRITERION - LI QingYun; WU XiuJu (Jixie qiangdu)
The depth of the pipeline depression has different influence on the safety of X60 pipeline steel,combining Oyane ductile fracture criterion with numerical simulation method to study damage degree of the pipeline. Establishing three dimensional spherical concave defect pipeline model by finite element software and solving the model,discussing internal pressure influence of the pipeline and the indenter size on the relationship between the depth of sag and the damage degree of oil and gas pipelines.The results show that: when the depth of the pipeline depression is in a certain range the internal pressure is beneficial to resist ductile rupture. Once the depth of the pit exceeds 100 mm,the internal pressure will increase the extent of damage of the pipeline.In the case of the ratio of wall thickness to pipe diameter and the constant pressure in the pipe,the smaller the size of the indenter,the more serious the damage degree increases with the depth of the depression. Under certain conditions,when the pipe sag depth exceeds the standard 7% pipe diameter,the degree of pipe damage still meet the integral value I > 1. The Oyane ductile fracture criterion can be applied to the evaluation of sags in engineering projects because of the limitation of sag depth evaluation criteria.